2018
DOI: 10.2147/cia.s190713
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diabetes mellitus on anterior segment of the eye

Abstract: Diabetes mellitus (DM) has been emerging as one of the most serious health problems worldwide. Ocular complications of DM are currently one of the major causes of blindness in developed countries, among which diabetic retinopathy is relatively well studied and understood. However, although ocular surface complications of DM are common, diabetic complications of anterior segment of the eye, such as, cornea, conjunctiva, and lacrimal glands, are often overlooked. DM is associated with progressive damage to corne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 105 publications
(168 reference statements)
0
69
0
3
Order By: Relevance
“…The prevalence of diabetes mellitus is increasing rapidly in the 21st century, due to obesity, an ageing population, lack of exercise and increased migration of susceptible patients, it will be up to 552 million by 2030 [34][35][36]. And inadequate glycemic control may contribute to increase the risk of microvascular complications in patients with DM [37][38][39]. Hyperglycemia is an essential factor of the development and progression of retinopathy and nephropathy [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of diabetes mellitus is increasing rapidly in the 21st century, due to obesity, an ageing population, lack of exercise and increased migration of susceptible patients, it will be up to 552 million by 2030 [34][35][36]. And inadequate glycemic control may contribute to increase the risk of microvascular complications in patients with DM [37][38][39]. Hyperglycemia is an essential factor of the development and progression of retinopathy and nephropathy [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic retinopathy is one of the most frequently cited and well-studied complication associated with DM, but uncontrolled DM can affect other parts of the eye, and this is often overlooked. As a result, eye care professionals often miss the impact of DM on the anterior segment of the eye like cornea, conjunctiva, lacrimal glands and lens that can also lead to severe visual loss and even blindness [6]. Diabetic keratopathy (DK) affects 47-64% of patients during the clinical course of DM, and it is mostly underdiagnosed [7].…”
Section: Of 24mentioning
confidence: 99%
“…Several previous studies reported important confounders such as ocular blunt trauma (ICD-9-CM codes 921.1, 921.2, 921.3 and 921.9), corneal abrasion (ICD-9-CM code 918.1), postcorneal transplantation (order codes 85 212B, 85 213B, 85 215B, 85 216B and 85 217B), corneal dystrophy (ICD-9-CM code 371.5) and band keratopathy (ICD-9-CM code 371.43) as potential comorbidities defined by the evident criteria mentioned earlier. [19][20][21] However, we could not evaluate whether these comorbidities were significant risk factors of RCE because of the low number of patients with these potential comorbidities or the low incidence of these potential comorbidities (online supplementary table 1S).…”
Section: Selection Of Patients and Variablesmentioning
confidence: 99%